PELAKSANAAN SUPERVISI AKADEMIK KEPALA MADRASAH DALAM MENINGKATKAN KINERJA GURU DI MAN 5 BARITO KUALA DAN MAS DARUL MUKARRAM KABUPATEN BARITO KUALA - Nordin, Ahmad; Husnul Madihah; Ani Wardah (Journal of Innovation Research and Knowledge, 2023)
Academic supervision is essentially an action that is attempted to assist teachers in developing their potential to manage learning so that it is better. The Madrasah head as a supervisor in carrying out his duties in carrying out academic supervision should have been carried out in a programmed and measurable manner. This study aims to describe (1) describe the academic supervision arranged by the head of the madrasa in improving teacher performance at MAN 5 Barito Kuala, (2) describe the academic supervision arranged by the head of the madrasa in improving teacher performance at MAS Darul Mukarram Barito Kuala Regency. This study uses a qualitative descriptive approach, which is a research procedure that produces descriptive data in the form of written or spoken data and people and behavior that can be observed as research objects. Implementation of academic supervision by the head of the madrasa at MAN 5 Barito Kuala and MAS Darul Mukarram Barito Kuala District. took samples and data sources from the Head of Madrasah Teachers and the Academic Supervision Team. Data collection techniques through interviews, observation and documentation. Based on the results of the study, it shows that: (1) The implementation of supervision at MAN 5 Barito Kuala is in accordance with the existing theory. By carrying out the observation phase which starts with planning, implementation, analysis and evaluation, as well as follow-up supervision, it has been able to improve teacher performance and teacher competency in the learning process. (2) The implementation of supervision at MAS Darul Mukarram, Barito Kuala Regency, is also in accordance with the existing theory. The supervision stage also begins with planning, implementation, analysis and evaluation, as well as follow-up supervision which has shown an increase in teacher performance in planning lessons, teacher competence, and teacher performance in the learning process.